2014
DOI: 10.1093/ehjci/jeu137
|View full text |Cite
|
Sign up to set email alerts
|

Young patients with hypertrophic cardiomyopathy, but not subjects at risk, show decreased myocardial perfusion reserve quantified with CMR

Abstract: Young individuals with HCM, but not those at risk, show decreased MP during hyperaemia compared with controls even in the absence of diastolic dysfunction or LV outflow obstruction. These results may suggest that microvascular disease contributes to the decreased MP in the investigated population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…The global myocardial perfusion data are overlapping with the results previously reported [31]. MP was decreased in the HCM group versus controls ( p  = 0.02), even when using Z score > 2.5 SD for HCM diagnosis, but no significant changes in MP were found in the HCM-risk group vs. controls (Fig.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The global myocardial perfusion data are overlapping with the results previously reported [31]. MP was decreased in the HCM group versus controls ( p  = 0.02), even when using Z score > 2.5 SD for HCM diagnosis, but no significant changes in MP were found in the HCM-risk group vs. controls (Fig.…”
Section: Resultssupporting
confidence: 88%
“…However, when using mitral E/e´ > 8 as a cut-off for LV diastolic dysfunction, we found higher levels of ICTP ( p  = 0.02) in the HCM group, a finding that could suggest alterations in ECM prior to development of fibrosis. As recently reported [31], the degree of myocardial fibrosis was assessed using CMR -LGE, and the association between regional hypoperfusion and fibrosis [39] in young patients with HCM. In line with previous studies showing a certain correlation between the magnitude of fibrosis and the degree of hypertrophy [2, 79], fibrosis was predominantly found in myocardial segments with advanced hypertrophy [39] and also indicating a pathology beyond LVH and LGE by showing greater extent of areas with impaired myocardial perfusion even in non-fibrotic myocardium during adenosine hyperemia indicating regional hypoxemia, suggesting an important relationship of myocardial hypoperfusion with fibrosis occurrence in HCM [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognostic value of LGE in HCM remains elusive [ 11 , 18 ], and ischemia has been proposed as an earlier marker of disease [ 4 , 29 , 32 ]. We have earlier showed that global perfusion is decreased in the same cohort of young patients with HCM investigated in the current study [ 12 ]. However, the relationship between regional perfusion, hypertrophy and fibrosis has not been studied in young HCM patients and HCM-risk subjects.…”
Section: Introductionmentioning
confidence: 60%
“…92 Assessment of coronary microvascular dysfunction is challenging and stress perfusion CMR imaging could have a future role in risk stratification. [94][95][96] Exercise capacity has also been proposed to help risk stratification in different studies. [97][98][99] It has been demonstrated that peak VO2 is associated with an increased risk of major events during short-term follow-up.…”
Section: Other Potential Risk Factors and Arbitrators Not Included Inmentioning
confidence: 99%